First, rewrite the equation in standard form:
x^2 + 7x + 10 = 0
Now, we can use the quadratic formula to solve for x:
x = (-b ± √(b^2 - 4ac)) / 2a
In this case, a=1, b=7, and c=10.
Substitute these values into the formula:
x = (-7 ± √(7^2 - 4*1*10)) / 2*1
x = (-7 ± √(49 - 40)) / 2
x = (-7 ± √9) / 2
x = (-7 ± 3) / 2
This gives us two possible solutions:
x = (-7 + 3) / 2 = -4 / 2 = -2
x = (-7 - 3) / 2 = -10 / 2 = -5
So the solutions are x = -2 and x = -5, which makes the correct answer: d. x = -2, -5
Use the quadratic formula to solve the equation. If necessary, round to the nearest hundredth.
x2 + 10 = –7x
(1 point)
Responses
a. x = 2, 5
b. x = –2, 5
c. x = 2, –5
d. x = –2, –5
1 answer